2019
DOI: 10.3389/fphar.2019.01267
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of the Effects of Buxin Yishen Decoction in Promoting Heart Function and Inhibiting the Progression of Renal Fibrosis in Myocardial Infarction Caused Type 2 Cardiorenal Syndrome Rats

Abstract: This study aimed to investigate the therapeutic effect of traditional Chinese medicine-Buxin Yishen decoction (BXYS) on type 2 cardiorenal syndrome (CRS) caused by myocardial infarction and explore the possible mechanism BXYS works. A chronic heart failure (CHF) rat model induced by left anterior descending coronary artery ligation was used and five groups were created that included a sham group, a CHF model group, a fosinopril group, a BXYS (0.4 g/kg) group and a BXYS (0.8 g/kg) group. Heart function, renal h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…The cardiac characteristics observed in this study are consistent with previous reports using this model of HF [41][42][43]. Additionally, substantial number of previous studies [44][45][46][47][48][49][50][51] demonstrated that natriuretic peptide levels in both the heart and the serum are significantly increased in rats with HF induced by coronary artery ligation used in the current study. Taken together, the ˃ 30% infarct size, increased LVEDP, LVEDD, LVESD, LVEDV and LVESV and decreased dP/dt, FS, EF, SV and CO all indicate that rats in HF group were experiencing cardiac dysfunction.…”
Section: Cardiac Characteristics Of the Hf Modelsupporting
confidence: 92%
“…The cardiac characteristics observed in this study are consistent with previous reports using this model of HF [41][42][43]. Additionally, substantial number of previous studies [44][45][46][47][48][49][50][51] demonstrated that natriuretic peptide levels in both the heart and the serum are significantly increased in rats with HF induced by coronary artery ligation used in the current study. Taken together, the ˃ 30% infarct size, increased LVEDP, LVEDD, LVESD, LVEDV and LVESV and decreased dP/dt, FS, EF, SV and CO all indicate that rats in HF group were experiencing cardiac dysfunction.…”
Section: Cardiac Characteristics Of the Hf Modelsupporting
confidence: 92%
“…Increased cardiac fibrosis is associated with augmented myocardial stiffness, cardiomyocyte necrosis, arrhythmias, sudden cardiac death and unfavorable prognosis, and plays an important role in the remodeling process that leads to HF ( Espeland et al, 2018 ). Increased renal fibrosis is a key contributor to the progressive decline in renal function with time ( Hewitson, 2009 ; Qiu et al, 2019 ). Consistent with previous studies ( Liu et al, 2013 ; Savira et al, 2020b ), VEH-treated MI + STNx rats had significant increases in cardiac and renal interstitial fibrosis and myocyte hypertrophy, which were associated with upregulation in gene expression of key pro-hypertrophic and pro-fibrotic markers.…”
Section: Discussionmentioning
confidence: 99%
“…It is well recognized that renal fibrosis caused by chronic heart failure is an important pathological feature of CRS2, which could develop into end-stage renal disease. 7 Heat shock protein 90 (HSP90) is one of the most abundant molecular chaperone proteins and is involved in cell survival, growth, and differentiation. 8,9 HSP90 has been reported to be activated in many fibrotic diseases, for example cardiac fibrosis, 10 renal fibrosis, 9 and pulmonary fibrosis.…”
Section: Introductionmentioning
confidence: 99%